STROKE ISKEMIK DENGAN MANIFESTASI DIZZINESSVERTIGO TERISOLASI - Diyan Anita Sari,* Sri Sutarni,* Ismail Setyopranoto* (Neurona Majalah Kedokteran Neuro Sains, 2020)
UNSTABLE WALKING OR LOSS OF BALANCE ARE SYMPTOMS IN ABOUT 50 OF STROKE CASES HOWEVER ONLY ABOUT 20 ARE ACCOMPANIED BY FOCAL NEUROLOGICAL SIGNS IN THE LAST DECADE THERE IS INCREASING EVIDENCE THAT VERTIGO CAN BE THE ONLY ISCHEMIC SYMPTOM OF POSTERIOR CIRCULATION STROKE WITHOUT A FOCAL SIGN THE PURPOSE OF THIS SYSTEMATIC REVIEW IS TO EXAMINE THE LITERATURE ON ISCHEMIC STROKE WITH THE MANIFESTATION OF ISOLATED DIZZINESSVERTIGO